Implications for practice: Resurgence and differential reinforcement of alternative responding. Issue 4 (19th October 2015) - Bloom, Sarah E.; Lambert, Joseph M.
Abstract : During the maintenance stages of differential reinforcement of alternative responding (DRA), failure to reinforce alternative responses could result in a resurgence of problem behavior. However, translational work done with arbitrary human responses suggests that teaching individuals to emit multiple alternative responses in sequential order may facilitate the resurgence of appropriate, rather than problem, behavior. This paper discusses the practical implications of serial DRA training on problem and appropriate behavior resurgence, as presented in the preceding article, "Serial Alternative Response Training As Intervention for Target Response Resurgence." Clinical scenarios as well as implications for self‐advocacy and acceptability of behavioral interventions are considered.